Assessment of red cell distribution width in patients with hematological malignancy - Athmar Khadihm Gatea; Mohammed Ali Al-Jabory; Ban Adnan Shamki; Aseel H. Al-Sabary (Iraqi Journal of Hematology, 2025)
BACKGROUND: Red cell distribution width (RDW) is one of the red cell parameters. It reflects the variation in the size and shape of red blood cells (RBCs). It changes in different disease processes. It has a role in evaluating the prognosis in patients with different cancer types, including hematological malignancies, reflecting the effect of inflammatory cytokines produced by malignant cells on the shape and size of RBC. In general, cancer-associated inflammation represents the hallmark of cancer development and progression. Based on these facts, many studies evaluate the role of RDW in the prognosis. RDW is associated with cancer-induced malnutrition and malabsorption, which causes hematinic deficiency, reflecting its correlation with poor prognosis. Furthermore, higher RDW is associated with higher cardiovascular and inflammatory risks, thus increasing the risk of chemotherapy-induced cardiotoxicity. OBJECTIVES: We assess the difference between RDW from healthy people and patients diagnosed with hematological malignancies. MATERIALS AND METHODS: This study was performed in Babylon Province, comparing the RDW difference between healthy people and hematological malignancy patients. A total of 148 participants, 74 of them were healthy people and 74 were newly diagnosed with hematological malignancies, 44 with myeloid malignancy, 30 with lymphoid malignancy. RESULTS: The mean RDW-coefficient of variation (CV) for healthy people was 13.33 ± 1.14, whereas that for patients was 16.12 ± 3.62 with a significant difference (P < 0.0001). Similarly, the mean RDW-standard deviation (SD) for healthy people was 45.01 ± 4.96, whereas that for patients was 57.10 ± 12.78 with a significant difference (P < 0.0001). Similarly, there is a significant difference in RDW-SD and RDW-CV between those with myeloid and lymphoid neoplasms as separately compared to healthy people (P < 0.0001). However, a significant difference was only found in RDW-CV in comparison between these two groups (P = 0.04). CONCLUSION: Measurement of RDW of both types is important for predicting the prognosis of hematological malignancies. However, it is limited to the determination of the significant difference in RDW between healthy people and patients who are newly diagnosed with hematological malignancies without studying RDW effect on disease prognosis.